BENCHMARKING THE PERFORMANCE OF ZAKAT INSTITUTIONS: A DEA-BASED EFFICIENCY ANALYSIS OF BAZNAS AT THE LOCAL GOVERNMENT LEVEL - Muhammad Aswad; Suminto (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to examine the efficiency level of the National Zakat Agency (BAZNAS) at the district and municipal levels in Indonesia, with a particular focus on managerial capacity, resource optimization, and strategies for zakat collection and distribution in improving institutional performance. This research employs a quantitative approach using the Data Envelopment Analysis (DEA) method to assess the relative efficiency of BAZNAS units. An input–output model is applied, where inputs consist of total assets and operational costs, while outputs include zakat collection and distribution. The study utilizes secondary data derived from the financial reports of selected BAZNAS institutions and conducts a comparative efficiency analysis across decision-making units. The results indicate that the efficiency levels of BAZNAS institutions vary significantly across regions, with only a limited number achieving full efficiency. Several institutions operate below optimal efficiency due to suboptimal asset utilization, high operational costs, and less effective zakat collection and distribution strategies. Furthermore, managerial capacity and the implementation of good governance principles are found to play a critical role in determining institutional efficiency. This study provides important implications for policymakers and zakat administrators in enhancing efficiency through strengthening managerial capacity, improving resource allocation, and adopting innovative, technology-based zakat management strategies. However, this research is limited by the relatively small sample size and reliance on secondary data, which may not fully capture qualitative aspects such as public trust and governance quality. This study contributes to the literature on Islamic philanthropy by integrating efficiency analysis using Data Envelopment Analysis (DEA) with a conceptual framework encompassing managerial capacity, resource optimization, and operational strategies at the local government level. The findings offer practical insights for improving zakat management performance and serve as a reference for future research and policy development.